Peramalan Kunjungan Wisatawan Interasional dan Domestik ke Manado Tahun 2015 dan 2016 - Kaloh, Mauren R. P. (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstract: The Vision of Manado government to make Manado as World Tourism city 2010 is a program and fundamental policy planning to create Manado safe, competitive, prosper, have justice and prestige. Program that sets by Department of Cultural and Tourism for 5 years are: (1) Increasing society participation in tourism development. (2) Develop the tourism human resources. (3) Develop tourism destination zone. (4) Program to maintain cultural diversity. (5) Develop tourism promotion. (6) Develop the usage of tourism information technology in Manado. The Scondary data that writer collect Statistic Central Office Manado, and from Cultural and Tourism Department Manado. Method that writer use is Least Square Method. Tourism development is relatively good, the capability value is also relatively good, but they still need to develop the potential object into international grade. The condition of tourism objects needs many repairmen include the facility and infrastructure to support tourism. The evaluation of infrastructures that support the tourism are relatively less. This forecasting needs to see the potency of Manado Tourism in the future The forecasting result of international tourist visits in Manado on 2015, has an increasing by 55% from 2010 and on 2016 the increasing is 64%. The forecasting result of domestic tourist visits in Manado on 2015, has an increasing by 36% from 2010 and on 2016 the increasing is 42%. Keywords : Tourism, Tourist, Culture